Tendencje w preferencjach i zwyczajach polskich konsumentów - Hamulczuk, Mariusz; Idzik, Marcin (Tendencies in Polish Consumer Preferences and Customs, 2005)
The article presents the decision making process by the consumers related to Fast Moving Consumers Goods purchases (including food). The research has shown that changes in Polish economy and globalisation trends have an influence on consumer's preferences and behaviours. Among others the growing value of the time for consumers, factors affecting shop choice and consumer's favourite means of promotion have been discussed.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 1, s. 327-331